The Use of Mentimeter to Improve Learning Interaction: A Classroom Action Research Study - Wawuk Retno Wulan; Dwi Sulisworo (Journal of Mathematics Science and Computer Education, 2023)
The primary objective of this study is to ascertain the usefulness of Mentimeter in improving learning interactions. The type of research used is classroom action research, conducted in a class of 18 seventh-grade students in the even semester of 2022-2023 at SMP Hidayatul Muhajirin. The research consists of two cycles, and the implementation of each cycle includes stages such as planning, implementation, observation, and reflection. The study discovered that the learning interaction activities among students consistently increased in each meeting, with an average of 67% in Cycle I and 78% in Cycle II. There was an increase of 11%, indicating good criteria. The improvement in learning interaction among students was due to the utilization of Mentimeter as a learning media. The Mentimeter application has various features that allow teachers to create interactive and engaging learning activities, such as quizzes, polls, and word clouds. The use of these features helps students to be more involved in the learning process and improves their understanding of the material. The research also found that Mentimeter can provide real-time feedback to both teachers and students. Teachers can track students' understanding of the material, and students can see their progress throughout the learning process. This feedback helps teachers adjust their teaching methods and materials according to students' needs. Based on the analysis and discussion of the research, it can be summarized that the use of Mentimeter can enhance the learning interaction of students. The use of Mentimeter can be recommended for teachers to improve the quality of learning interactions and create a more engaging and interactive learning environment.